2022
DOI: 10.3389/fmicb.2022.851567
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Analysis Revealed Differences in Composition and Function Between Liquid-Associated and Solid-Associated Microorganisms of Sheep Rumen

Abstract: The rumen microbiota plays a key role in the utilization of plant materials by ruminants, yet little is known about the key taxa and their genetic functions of the rumen sub-environment involved in the ruminal degradation process. Understanding the differences in the composition and function of ruminal microbiota in the liquid-associated (LA) and solid-associated (SA) systems is needed to further study and regulate rumen function and health. In this study, rumen contents of nine sheep were collected to separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Thus, we speculate that the function of the genus Ruminococcaceae NK4A214 group may be related to degradation of soluble carbohydrates. Although accounting for a relatively small proportion, the high fibrolytic activity makes genera Fibrobacter and Ruminococcus play a nonnegligible role in fiber degradation [ 73 ]. Supplementation of ECP with 6 g/kg of substrate increased the relative abundance of the genera Fibrobacter and Ruminococcus , which could result in the increase of the concentration of total VFAs at 24 h (63.8 vs. 71.6 mmol/L).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we speculate that the function of the genus Ruminococcaceae NK4A214 group may be related to degradation of soluble carbohydrates. Although accounting for a relatively small proportion, the high fibrolytic activity makes genera Fibrobacter and Ruminococcus play a nonnegligible role in fiber degradation [ 73 ]. Supplementation of ECP with 6 g/kg of substrate increased the relative abundance of the genera Fibrobacter and Ruminococcus , which could result in the increase of the concentration of total VFAs at 24 h (63.8 vs. 71.6 mmol/L).…”
Section: Discussionmentioning
confidence: 99%
“…The rumen is a fermentation vat containing a large number of microorganisms, which are closely associated with these results. Our previous studies have shown that there are significant differences in composition and function between SA and LA microbes in the rumen [ 15 ]. Therefore, we decided to investigate the effect of YP on the microbial composition in these two different systems.…”
Section: Discussionmentioning
confidence: 99%
“…Rumen liquid-associated (LA) microorganisms and solid-associated (SA) microorganisms were extracted using the method from a previous publication [ 15 ]. After acquiring 50 mL of rumen fluid, it was filtered with four layers of sterilized cheesecloth and centrifuged at 10,000 g for 20 min at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations